2010
DOI: 10.1128/iai.00916-09
|View full text |Cite
|
Sign up to set email alerts
|

A New Generation of Stable, Nonantibiotic, Low-Copy-Number Plasmids Improves Immune Responses to Foreign Antigens in Salmonella enterica Serovar Typhi Live Vectors

Abstract: We hypothesized that adequately engineered attenuated Salmonella enterica serovar Typhi strains can serve as multivalent mucosal live vector vaccines to immunize against unrelated human pathogens. Toward this ultimate goal, we have developed a novel genetic stabilization system for antigen-expressing plasmids, engineered to encode the single-stranded binding protein (SSB), an essential protein involved in DNA metabolism which was deleted from the live vector chromosome. We utilized full-length protective antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 43 publications
2
38
0
1
Order By: Relevance
“…Similar to the pattern of humoral responses to Ag85A, the antibody response against ESAT-6 was inversely related to the copy number of the plasmids, suggesting that a metabolic burden was imposed on the RASV by the synthesis of the protective antigens. A similar observation has been described previously, where the immune response to antigens delivered by Salmonella Typhi vaccines was improved when the ClyA-PA83 antigen was expressed from low-copy-number plasmids (pSC101 ori), which induced the highest antibody responses (32). In this study, the highest anti-ESAT-6 IgG titers were observed in the mice vaccinated with 11021(pYA4894 [p15A ori]) alone or in mice vaccinated simultaneously with both 11021(pYA4894) and 11021(pYA4892 [pSC101 ori]).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Similar to the pattern of humoral responses to Ag85A, the antibody response against ESAT-6 was inversely related to the copy number of the plasmids, suggesting that a metabolic burden was imposed on the RASV by the synthesis of the protective antigens. A similar observation has been described previously, where the immune response to antigens delivered by Salmonella Typhi vaccines was improved when the ClyA-PA83 antigen was expressed from low-copy-number plasmids (pSC101 ori), which induced the highest antibody responses (32). In this study, the highest anti-ESAT-6 IgG titers were observed in the mice vaccinated with 11021(pYA4894 [p15A ori]) alone or in mice vaccinated simultaneously with both 11021(pYA4894) and 11021(pYA4892 [pSC101 ori]).…”
Section: Discussionsupporting
confidence: 57%
“…Stability of the recombinant plasmids was determined for approximately 50 generations of bacterial growth in LB medium under selective and nonselective (presence of DAP) conditions as described previously (22,32,57,67).…”
Section: Construction Of Asdmentioning
confidence: 99%
“…This was digested with EcoRI and ligated into pSEC10. This plasmid carries the hok-sok genes for stable maintenance in the absence of antibiotics and is related to pSEC10S-83 (32).…”
Section: Methodsmentioning
confidence: 99%
“…An additional advantage of the P rhaBAD promoter was its decreased level of AdiA protein synthesis. Protein overproduction has been shown to impair the efficacy of Salmonella vaccines (48,49). For these reasons, we selected the ⌬P adiA276 ::TT rhaSR P rhaBAD adiA mutation for use in further studies.…”
Section: Figmentioning
confidence: 99%